Strategi Literasi Keuangan Sebagai Faktor Pendukung Keberlanjutan Usaha Mikro Kecil dan Menengah - Isna Ardila; Hastina Febriaty; Rini Astuti (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2021)
This research was conducted with the aim of obtaining results in the form of a financial literacy strategy in financial management to support the sustainability of culinary SMEs in the city of Medan. There are 100 samples used in this study obtained from purposive sampling technique. To obtain data, personal interviews were conducted with respondents and filled out questionnaires. The data analysis method uses Confirmatory Factor Analysis (CFA) to detect the dominant financial literacy factors by using the SEM (Structural Equation Model) structural equation model. Based on structural model testing, financial literacy strategies are obtained, namely financial behavior, financial socialization, and bookkeeping systems, and financial literacy strategies are proven as supporting factors for the sustainability of micro, small and medium enterprises.